Selection, performance and economic evaluation of dust palliatives on surface mine haul roads - Thompson, Roger; Visser, A. (SAIMM, 2007)
Excessive dust generation from unpaved mine haul roads is a problem common to most surface mining operations. While optimal road wearing course material selection parameters reduce the inherent dust generation potential, they do not totally eliminate fugitive dust. Many different classes of suppression or palliative treatments are available for mine haul roads and this paper initially ascertains basic selection guidelines, using a set of ideal dust palliative product, application and performance parameters based on mine road-user requirements. An evaluation and modelling methodology for truck generated fugitive dust emissions is developed as a basis for the comparative assessment of dust control strategies. For water-based spraying, a watering model was developed to estimate individual mine road watering frequencies for characteristic site parameter combinations during summer and winter operating conditions, for a required level of control or maximum dust defect. This forms the base-case scenario with which to compare the performance of other types of dust palliatives under the same conditions.Finally, a basic palliative economic evaluation model is introduced with the aim of identifying and costing the establishment, application and maintenance rejuvenation activities associated with the use of chemical palliatives. While palliative cost and performance is generally site specific, it is shown that under certain combinations of conditions, the use of dust palliatives has the potential to deliver cost savings when compared to water-based spraying.